1993
DOI: 10.1093/intimm/5.9.1151
|View full text |Cite
|
Sign up to set email alerts
|

An autoantigenic T cell epitope forms unstable complexes with class II MHC: a novel route for escape from tolerance induction

Abstract: The peptide rAc1-11 represents the dominant T cell epitope of rat myelin basic protein (MBP) in mice of the H-2u haplotype. Residue 4 has been shown previously to govern binding of the peptide to the class II molecule, I-Au. We have constructed peptide analogues bearing amino acid substitutions at position 4 and have assessed their ability to stimulate an antigen-specific T cell hybridoma when presented by viable antigen presenting cells (APC). Complexes between I-Au and one such analogue, rAc1-11[4A], were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 0 publications
11
127
0
Order By: Relevance
“…The extent and specificity of these self peptide-MHC complexes in facilitating activation of antigen-specific T cells needs to be examined in greater detail. As a side note, earlier work in the experimental autoimmune encephalomyelitis model had also suggested a relationship between low affinity peptides and T cell autoreactivity [46,47]. In this inducible disease model, the autoantigenic peptide, Ac1-11 of myelin basic protein, bound poorly to the class II MHC molecule, I-A u , and autoreactive T cells were shown to escape negative selection in the thymus [46,47].…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thmentioning
confidence: 76%
“…The extent and specificity of these self peptide-MHC complexes in facilitating activation of antigen-specific T cells needs to be examined in greater detail. As a side note, earlier work in the experimental autoimmune encephalomyelitis model had also suggested a relationship between low affinity peptides and T cell autoreactivity [46,47]. In this inducible disease model, the autoantigenic peptide, Ac1-11 of myelin basic protein, bound poorly to the class II MHC molecule, I-A u , and autoreactive T cells were shown to escape negative selection in the thymus [46,47].…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thmentioning
confidence: 76%
“…In the case of the diabetic NOD mouse, previous studies (36,37) identified a high number of autoreactive T cells. These were attributed to the I-A g7 molecule, indicating that this MHC molecule in general had a propensity for high autoreactivity.…”
Section: Discussionmentioning
confidence: 96%
“…The PI-1(47-64) epitope represents a striking example of a very poor binding MHC ligand, IC 50 values ϳ100 mol/l, that gives rise to T-cells capable of causing diabetes in adoptive transfer experiments. The relationship between poor peptide-MHC binding and the fostering of an autoimmune, pathogenic T-cell repertoire has been suggested in studies on experimental allergic encephalomyelitis (7,8) and in our recent work on the insulin ␤-chain (9 -23) epitope (2) and in other model systems (9 -11).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of low affinity of a peptide to an MHC molecule and autoimmune reactivity has also been noted in the encephalitogenic peptide from myelin basic protein (7,8). This has led to the speculation that low-affinity peptides may not be conducive to the normal mechanisms in the thymus that control autoreactivity.…”
mentioning
confidence: 99%